2014
DOI: 10.4012/dmj.2013-227
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength and microleakage of self-adhesive and conventional fissure sealants

Abstract: The aim of this study was to compare the shear bond strengths (SBS), failure modes (adhesive, cohesive, or mixed), and marginal microleakage occurrence of conventional resin (CR)-based, glass ionomer (GI)-based, and self-adhesive resin (SAR)-based fissure sealants with or without prior phosphoric acid (PA) etching. Fifty extracted premolars were randomly and equally assigned into five groups -G1:PA+CR, G2:PA+GI, G3:GI, G4:PA+SAR, and G5:SAR. Prior PA etching significantly (p<0.05) increased the SBSs of sealant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Insufficient penetration ability also makes them less retentive mechanically when compared with the opponents. The study results revealed that glass-ionomer-based sealants showed the least penetration depth with more microleakage, in harmony with previous studies 31,32) . The chemistry of resin-based sealants is not different from the composites used for dental restorations.…”
Section: Non-invasive Enameloplastysupporting
confidence: 79%
“…Insufficient penetration ability also makes them less retentive mechanically when compared with the opponents. The study results revealed that glass-ionomer-based sealants showed the least penetration depth with more microleakage, in harmony with previous studies 31,32) . The chemistry of resin-based sealants is not different from the composites used for dental restorations.…”
Section: Non-invasive Enameloplastysupporting
confidence: 79%
“…Regarding the mode of failure, VF showed significantly lower adhesive failure than Clinpro sealant and PLP group. The lower tendency towards adhesive failure of the VF may thus be attributed to its higher bond strength together with the effect of PA over the enamel surface during conditioning (31).…”
Section: Discussionmentioning
confidence: 99%
“…The sealants are able to penetrate to a depth of 25–50 µm, thus providing a resistant and effective bond between the sealant and enamel. 24,25 Polyacrylic acid etching provides good wetting of the tooth surface and produces a chemical interaction between the glass ionomer and the mineral phase of the enamel. 24 20% polyacrylic acid was used to condition the tooth surface before sealant application.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Polyacrylic acid etching provides good wetting of the tooth surface and produces a chemical interaction between the glass ionomer and the mineral phase of the enamel. 24 20% polyacrylic acid was used to condition the tooth surface before sealant application. 20% polyacrylic acid application has also been reported to provide good SBS.…”
Section: Discussionmentioning
confidence: 99%